Measurement of X-Ray Radiation Exposure in Thorax Examinations at Radiology Installation of Wajak Husada General Hospital - Sugiarti, Sri; Wahyuni, Farida; Anisa, Dewi Okta Nur (Universitas Islam Negeri (UIN) Mataram, 2023)
The Study aims to measure radiation exposure on X-ray aircraft on chest radiography at the Radiology installation at Wajak Husada General Hospital. Measurements were carried out on the X-ray source tube and in the X-ray room environment at Wajak Husada General Hospital. This research aims to determine the value of radiation exposure and whether the examination room is safe for workers and the general public. Data collection in this research was direct observation in the radiology examination room; then, radiation exposure using a survey meter at points around the X-ray room. The highest exposure to X-ray aircraft was in the control panel room, which was 0.19 µSv/h or 0.88 mSv/y and was still below the dose limit value set by the Regional Head of Bapeten Regulation Number 4 of 2020, namely the dose limit value for workers of 20 mSv/ year and the community it is one mSv/year, concluded that the X-ray aircraft and environment are suitable for use and safe to occupy to implement radiology services.